2022
DOI: 10.14245/ns.2143186.593
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome After Spinal Meningioma Surgery. A Nationwide Population-Based Study

Abstract: Objective: To describe and analysed the functional outcome (FO) after spinal meningioma (SM) surgery.Methods: We processed the système national des données de santé (SNDS) i.e. , the French national administrative medical database to retrieve appropriate cases. We analysed the International Classification of Diseases 10 codes to assess the FO. Logistic models were implemented to search for variables associated with a favourable FO i.e. , a patient being independent at home without disabling symptom.Results: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Three studies only including adults (>18 years) reported 28 cases among 3063 patients (0.9%) [ 4 , 55 , 56 ]. The lower percentage in these studies may indicate that a significant number of these patients are diagnosed before reaching adulthood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies only including adults (>18 years) reported 28 cases among 3063 patients (0.9%) [ 4 , 55 , 56 ]. The lower percentage in these studies may indicate that a significant number of these patients are diagnosed before reaching adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…Age was positively correlated to motor symptoms in three studies [ 4 , 55 , 65 ], to sensory deficits in two studies—one of which with non-significant results [ 4 , 65 ]—gait, and bladder and bowel deficits in one study [ 55 ], and to none of the symptoms in another study [ 63 ]. In one of these studies including a total of 2844 patients, the authors stated that the symptoms were more severe in the elderly population.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to highlight that no explicit analysis has been conducted for outcomes in older patients. Similarly, in another SM study based on claim data, patients aged 70 years and older were significantly burdened by higher degrees of disability than occurred in younger patients (49.6% vs. 30.5; p < 0.001) [ 23 ]. However, surgical resection of SMs resulted in substantial amelioration of patients’ functional status, although older patients require more time for recovery, which is apparently due to their clinical vignette [ 23 ].…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, in another SM study based on claim data, patients aged 70 years and older were significantly burdened by higher degrees of disability than occurred in younger patients (49.6% vs. 30.5; p < 0.001) [ 23 ]. However, surgical resection of SMs resulted in substantial amelioration of patients’ functional status, although older patients require more time for recovery, which is apparently due to their clinical vignette [ 23 ]. Older age at a given level of surgery and higher rates of underlying conditions were significant risk factors for less favorable outcomes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation